Planning for the Future: A Land-Use and Transport Interaction Model for Switzerland - Balz R. Bodenmann; Breogan Sanchez; Alexandra Zeiler; Milan Kuliowsky; Peter Furtak; Georgios Sarlas (European Regional Science Association (ERSA), 2014)
Spatial and transport planners, authorities, real estate developers, investors, re-locating residents and businesses have different questions related to space and transport. These questions may concern specific land parcels, or cover a much larger area such as a city, a region, or even a whole nation. Amongst others, these questions include: - How will our society respond to influences of global economy and political decisions (e.g. regarding demographics and firmographics)? - Which strategies will help authorities and politicians to reach their goals? - What are the spatial effects (and side-effects) of these decisions and demographic changes (e.g. spatial/social segregation, use of resources and infrastructure, climate impact)? To answer these questions, different scenarios have been simulated including all 3000 municipalities in Switzerland using the integrated transport and land use simulation tool FaLC (Facility Location Choice Simulation Tool). FaLC incorporates interactions between land use, transportation, economy and public policy and has been developed in a joint project between the Institute for Transport Planning and Systems (IVT) at ETH Zurich, regioConcept (Switzerland) and ESMO (Slovakia). The models in FaLC focus on the effects of changing infrastructure supply, political decisions, and economic conditions on the spatial behaviour (location and relocation choices, transport flows) of persons (places of residence, work, leisure and shopping), firms (domicile, branches) and goods (freights, wholesale, retail, cash flow). In FaLC, persons move (or stay) in a certain space divided into a number of subareas (locations), comparable to a chess board. The agents' movement includes the daily commuters between home, work and leisure, as well as long-term decisions such as; where they live, work and generally spend their spare time. The first prototype of FaLC is already in operation and ready to create future scenarios. The implemented case study for Switzerland focusses basically on three scenarios: - Effects of road network modification - Effects of company taxes reduction - Effects of land regulation modification This paper shows the effects and side-effects of these assumed spatial interventions. Additionally, it discusses some problems of the chosen micro-simulation approach (e.g. data availability, white noise, choice of subsets).
Keywords: H30; J10; J20; R11; R12; R30; R42; R52; R58; 330; Spatial Planning; Land Use; Transport; Scenarios; Simulation; Urban Policy